Transformations and Challenges of Polish Educational Policy - Social Assessment and Future Perspectives - Mateusz Dominik Nesterok (Rozprawy Społeczne)
Abstract The article presents the results of research on the social perception of several aspects of Polish educational policy, including the assessment of the latest proposed changes in the Polish education system and the idea of introducing gamification and game-based learning into Polish schools.